A cidade em discussão: dinâmica urbana e redes sociais em Jardinópolis-SP (1926-1987) - Ferreira, Priscila Fernanda (2017)
The present work aims to present an interpretation about the urban dynamics in the county of Jardinópolis, between the years of 1926 to 1987. In order to achieve this, we have collected a variety of sources: newspapers, city plans, photographs, laws, bills and parish records. In this sense, in the first part of our dissertation, we intend to characterize the urbanization project that had been implemented in the city since the beginning of the 20th century, as well as to identify the interests of which groups the accomplishment of this task served. More specifically, in the second chapter, we intended to address the episode in which the transference of the residents of “Vila Sebosa” to the "Cidade Operária” occurred, being moved from the center to the peripheral area of Jardinópolis in 1964. In this phase of our analysis, we work with the composition of networks, in order to recognize the central role of the social actors in this transformation process of the city. At the end of our text, we intend to demonstrate how the urban configuration of Jardinópolis was changed after the creation of a periphery that, until then, did not exist in the county. We point out that, as a result of the consolidation of "Vila Reis" neighborhood - formerly "Cidade Operária" - the city has been expanding to new areas, increasingly distant from the center, where demand for popular houses was met. In the meantime, we sought to expose the positive propagation of the public image of Newton Reis - mayor who was the author of the law project which intended to remove the residents of “Vila Sebosa” from the center to the "Cidade Operária" - as one of the best politicians that Jardinópolis has ever had, highlighting how this promotion was made after the realization of the episode presented.